Figure 4 from: Elvebakk A, Bjerke JW (2024) Papaver recircumscribed: A review of neighbouring Papaveraceae genera, including Afropapaver nom. et stat. nov. and Oreomecon, a large, Arctic-Alpine genus. PhytoKeys 248: 105-188. https://doi.org/10.3897/phytokeys.248.121011 - Elvebakk, Arve; Bjerke, Jarle W. (Zenodo, 2024)
Figure 4 World distribution of the genera Afropapaver (green), Papaver (red), Parameconopsis (grey) and Stylomecon (violet). See Table 1 for species number per genus.